Chemical Composition and Bioactivity Dataset Integration to Identify Antiproliferative Compounds in Phyllanthus Plants - Luis Diaz; Taylor H. Díaz-Herrera; Ericsson Coy-Barrera (Pharmaceutics)
Background/Objectives: Phyllanthus species are renowned in traditional medicine for their diverse therapeutic properties, including potential anticancer activities. This study explored the antiproliferative potential of six Phyllanthus species by integrating chemical composition with bioactivity assays to identify key antiproliferative compounds. Methods: The integration of liquid chromatography–mass spectrometry (LC-MS)-based chemical composition data with antiproliferative activity against three cancer cell lines—PC-3 (prostate adenocarcinoma), SiHa (cervical carcinoma), and A549 (lung carcinoma)—as well as a normal mouse fibroblast line (L929) was performed by covariate analysis. These compounds were subsequently isolated and structurally characterized using spectroscopic methods. Results: Through covariate statistics, seven m/z features were found to be plausible active compounds, and after isolation, they were related to butyrolactone and arylnaphthalide lignans. Among the active isolates, an unreported compound, (+)-phyllanlathyrin 6, was discovered in the aerial part of Phyllanthus lathyroides. The isolated compounds exhibited moderate to good antiproliferative activity (IC50 < 20 µM) with selectivity to SiHa, validating the covariate-based identification approach. Conclusions: These findings highlight the potential of Phyllanthus species as sources of novel anticancer agents, with specific arylnaphthalide lignans showing promising cytotoxic effects that could be further developed into therapeutic leads. Additionally, this study underscores the value of combining advanced analytical techniques with bioactivity testing to uncover bioactive compounds from natural sources. The results contribute to the growing body of evidence supporting the therapeutic relevance of Phyllanthus species and provide a foundation for future drug development efforts targeting cancer treatment.